Exploring critical issues of technical support in contact centers of the Philippines: Toward a grounded theory - Apag, Meldie A. (Animo Repository, 2017)
The contact center industry in the Philippines, named by Deloitte as one of the two top contact center destinations in Asia, has been expanding rapidly in terms of technology, workforce size, and economic scope. This study aims to explore, using the Glaserian grounded theory method (GTM), the main concern of contact center agents, particularly inbound technical support representatives, in Northern Mindanao in the Philippines, and how they resolve their main concern, especially using information technology. GTM goes beyond the descriptive approach of most qualitative methods by generating from the data, a theory of the substantive area. The rationale for GTM reflects the source of the developed theory grounded in the behavior, words, and actions of those under study. The theory can inform the development of systems, processes, structures, and policies that will support the actors in the substantive area. Preliminary results suggest that staying at the organization or else seeking other employment opportunities is the main concern of the technical support representatives, who resolve this main concern using a cyclical process, each cycle of which has four stages: training, struggling, coping, and motivating. The application of technologies in contact center operations can play a key role in sustaining the technical support representatives' decision to stay longer in the industry. Copyright © 2017 ACM.